Is there a crack epidemic among students in Brazil?: comments on media and public health issues Há uma epidemia de crack entre estudantes no Brasil?: comentários sobre aspectos da mídia e da saúde pública - Solange Aparecida Nappo; Zila M. Sanchez; Luciana Abeid Ribeiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
In the past year, the Brazilian Federal Government and society have reported and acted on a crack use epidemic, which has been exacerbated by the media. This study hypothesized that crack use has not increased at the rate suggested by the Brazilian media. A cross-sectional survey was carried out in 2010 usinga multistage probabilistic representative sample of Brazilian middle and high school students in the country's 27 state capitals. A total of 50,890 valid questionnaires were weighted, analyzed and results compared to the 2004 national school survey dataset. Considering lifetime and past year crack use, no change in consumption was found between 2004 and 2010. Official data in Brazil on middle and high school students does not support the assertion of a crack epidemic widely publicized by the media. Government measures to treat and prevent crack use are encouraged; however, the term epidemic has been inappropriately used to represent the static prevalence of crack consumption among students. No último ano, o Governo Federal e a sociedade brasileira relataram e agiram em função de uma epidemia de crack, que foi exacerbada pela mídia. Este estudo hipotetiza que, entre estudantes, o consumo de crack não aumentou nas taxas propostas pela mídia brasileira. Um levantamento epidemiológico de corte transversal foi realizado em 2010 em uma amostra probabilística multiestágio de estudantes brasileiros de Ensino Fundamental e Médio das 27 capitais de estado. Os 50.890 questionários válidos foram submetidos a pesos amostrais, analisados e comparados à série de dados do mesmo levantamento nacional realizado em 2004. Considerando uso na vida e uso no ano de crack, nenhuma mudança do consumo foi encontrada entre de 2004 e 2010. Os dados oficiais brasileiros entre estudantes de Ensino Médio e Fundamental não corroboram "a epidemia de crack" divulgada extensamente pela mídia. Medidas do governo para tratar e prevenir o uso de crack são incentivadas; entretanto, o termo epidemia tem sido usado de maneira imprópria para representar a prevalência estática do uso de crack.